Towards assessment of plasma edge transport in Neon seeded plasmas in disconnected double null configuration in EAST with SOLPS-ITER. (March 2021) - Boeyaert, D.; Wiesen, S.; Wischmeier, M.; Dekeyser, W.; Carli, S.; Wang, L.; Ding, F.; Li, K.; Liang, Y.; Baelmans, M.; ,
Abstract: Energy dissipation in the plasma edge is key for future tokamaks. The potential of neon as radiating seeding species in disconnected double null (DDN) configuration is assessed in EAST discharges in high confinement mode (H-mode). As the separation between the two separatrices in the studied DDN discharges is minimum 1.5 cm, the configuration is effectively a single null configuration, and the benefits of the double null topology are minimal. Neon seeding, on the other hand, has a favourable effect: both the target heat flux and the divertor temperature decrease more than five-fold with increased seeding rate in high-recycling conditions. Interpretive edge plasma simulations with SOLPS-ITER in support of ongoing transport analysis are presented. For the unseeded case the numerical results agree with the experimental data within a factor two for the target temperature conditions and measured neutral pressures in the active divertor. The key for achieving good agreement is a suitable selection of coefficients for anomalous transport and neutral conductances between the upper cryopump and the main chamber. Highlights: Neon was used to increase the level of dissipation in the EAST low-field side upper divertor Due to Neon, a high-recycling regime was established A full detached regime was not achieved due to the limitations on input power. No clear advantages of DDN configuration were observed as the minimal drsep was larger than the power decay length. SOLPS-ITER simulations are set up to study performed discharges.